Thermoelectric device for cooling very large scale integrated circuits - Даналакий, Олег Григорьевич (Technology audit and production reserves, 2012)
The main purpose is to replenish the arsenal of hardware components thermoelectric elements that were previously unknown, on the one hand, and on the other - the study of the physical processes occurring in the known termoelementov with the boundary conditions that have not been used